Experimentation on generating two-dimensional quasi-random sequences - Chương, Vũ Hoài (Journal of Computer Science and Cybernetics, 2012)
<span lang="VI" style="font-family: "Times New Roman","serif"; font-size: 11pt; mso-ansi-language: VI; mso-fareast-font-family: "Times New Roman"; mso-fareast-language: VI; mso-bidi-language: AR-SA; mso-bidi-font-size: 12.0pt;">Halton/Hammersley sequences, the most well-known and widely used multi-dimensional quasirandom sequences, are constructed by combining van der Corput sequences with on another or with k/N sequence. We attempt to generate two-dimensional sequences by combining two simple one-dimensional sequences (k/N, mid-point, V, van der Corput, Richtmyer, pseudorandom sequences) and experimentally receive many lowest discrepancy sequences.